PENGARUH BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Subsektor Manufaktur yang Terdaftar di BEI pada Tahun 2017 – 2019) - Agnes Margareth Siregar; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The purpose of this study is to analyze the effect between deferred tax expense and tax planning on earnings management. The research method is descriptive with a quantitative approach. The data used in this study from annual financial statements on manufacturing companies that listed on the Indonesia Stock Exchange. Based on the simultaneous test results, deferred tax expense and tax planning have a significant effect on earnings management.